METHODOLOGY OF TEACHING ENGLISH IN HIGHER EDUCATION (Journal of Universal Science Research, 2026)
This article discusses the methodology of teaching English in higher education institutions. It analyzes modern pedagogical approaches, innovative technologies, student-centered learning, communicative competence development, and assessment strategies. The role of digital tools and interactive methods in improving language proficiency is also examined. Practical recommendations for effective English language instruction at universities are provided.